1991
DOI: 10.1029/91wr00076
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological impacts of changing land management practices in a moderate‐sized agricultural catchment

Abstract: Since the mid‐1930s a variety of soil conservation practices have been applied to agricultural lands throughout the United States. While intended to reduce soil erosion, if effective, these practices should alter the hydrology of streams which drain the treated lands. This hypothesis was explored for the East Branch of the Pecatonica River, a gaged 221 square mile agricultural catchment in southwestern Wisconsin. On the basis of the analysis of peak and daily flow data there has been a decrease in flood peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(138 citation statements)
references
References 6 publications
9
129
0
Order By: Relevance
“…While significant research focuses on the impacts of forest harvesting on streamflow (e.g., [27][28][29]) studies also include agriculture (e.g., [30]), and urbanization (e.g., [31][32][33]). …”
Section: Landuse and Land Cover Changesmentioning
confidence: 99%
“…While significant research focuses on the impacts of forest harvesting on streamflow (e.g., [27][28][29]) studies also include agriculture (e.g., [30]), and urbanization (e.g., [31][32][33]). …”
Section: Landuse and Land Cover Changesmentioning
confidence: 99%
“…Both the removal of streamside vegetation and increased impervious surface typically result in increased surface runoff and hydrologic variability (Trimble et al, 1987;Potter, 1991). These changes, in turn, lead to increased rates of erosion, increased loads of suspended and deposited fine sediments (Glenn, 1911;Ellis, 1936;Magilligan & Stamp, 1997), and elevated nutrient concentrations (Paul & Meyer, 2001;Groffman et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…A study by Potter (1991) attributed increased baseflow in a stream in eastern Wisconsin to advances in farming practices that resulted in increased recharge. A streamflow-trend study by Gebert and Krug (1996) concluded that decreased flood peaks and increased annual low flows in streams from the Wisconsin Driftless Area were caused by changes in agricultural practices and land use.…”
Section: Analysis Of Streamflow Trendsmentioning
confidence: 99%